2013
DOI: 10.2134/agronj2013.0031
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Chemical Attributes of Oxisol Subsoil and Crop Yields under No‐Till

Abstract: The natural chemical qualities of the subsoil of Oxisols often restrict root growth, water use efficiency, and crop yield. The practice of continuous no-till farming creates a fertile topsoil but generally does not affect the subsoil. This study aimed to evaluate the effectiveness of gypsum in improving the chemical attributes of the subsoil and increasing crop yields. To this end, the experiment was conducted at two sites in distrophic Red Oxisols located in southern Brazil. The experimental design was a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 34 publications
3
41
0
3
Order By: Relevance
“…In addition, ion pair formation of Al with SO 4 + (AlSO 4 + ) in the soil solution, which is a major mechanism for reducing the activity of aluminum (Al 3+ species). The formation of AlSO 4 + ions, which have a lower valence than Al +3 , increases the mobility in the soil profile and reduces aluminum saturation (Nora and Amado, 2013).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ion pair formation of Al with SO 4 + (AlSO 4 + ) in the soil solution, which is a major mechanism for reducing the activity of aluminum (Al 3+ species). The formation of AlSO 4 + ions, which have a lower valence than Al +3 , increases the mobility in the soil profile and reduces aluminum saturation (Nora and Amado, 2013).…”
Section: +mentioning
confidence: 99%
“…Under these conditions, root growth is restricted and thus limiting the access to water and nutrients available in the soil profile (Sousa and Lobato, 2004;Caires et al, 2006;Almeida et al, 2015). Agricultural or mineral gypsum (CaSO 4 .2H 2 O) is being widely used as source of nutrients such as calcium and sulfur and to adjust aluminum toxicity in the deeper soil layers (Caires et al, 2006;Nora and Amado, 2013), after correction of the pH in the surface layer by liming. Some studies have indicated that gypsum is an important complement to liming in the presence of high Al 3+ levels in the subsoil (Soratto and Crusciol, 2008;Caires et al, 2010;Crusciol et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…O coeficiente de variação observado para a CEa foi de 34,02% (camada 0,0-0,3 m) e 33,64% (camada 0-0,90 m), para a área 1, e de 40,41% (0,0-0,3 m) e 43,32% (camada 0,0-0,9 m), para a área 2 (Tabela 1). Valente et al (2012) , CTC e SB (Tabela 2), atributos que afetam de forma direta a produtividade de milho (Dalla Nora & Amado, 2013). Além destes, a matéria orgânica do solo (MOS) e a argila também se relacionaram positivamente (p<0,01) com a CEa.…”
Section: Resultsunclassified
“…agropec. bras., Brasília, v.51, n. , compromete a produtividade e a eficiência do uso da água pela cultura do milho (Dalla Nora & Amado, 2013). Carmo (2014) também evidenciou relação significativa entre a CE e os atributos químicos determinantes da acidez.…”
Section: +unclassified
“…O aumento do pH nas camadas mais profundas avaliadas proporcionado pela aplicação de gesso está associado ao deslocamento de hidroxilas (OH -) das superfícies dos óxidos e hidróxidos de ferro e alumínio por íons de sulfato (SO 4 -2 ), quando dissociados do cálcio (Ca 2+ ), conhecido como auto-calagem (Reeve & Summer, 1972;Caires et al, 2003;Rampim et al, 2011 (Pavan & Volkweiss, 1985;Raij, 1992;Nora & Amado, 2013 . O aumento nos teores de Ca 2+ trocável no perfil do solo após a aplicação de gesso tem sido reportado em muitos trabalhos (Caires et al, 2006;Santos et al, 2013;Pauletti et al, 2014) (Pavan & Volkweiss, 1985;Serafim et al, 2012 (Raij, 2008).…”
Section: Determinação Da Produtividade De Colmos E Qualidade Tecnológicaunclassified